Strain variation in feeding response of house flies, Musca domestica, to denatonium benzoate, a bittering agent used in commercial fly baits - Panchalie B. Gunathunga; B. H. King; Edwin R. Burgess I.V. (PLoS ONE, 2025)
Granular fly baits remain one of the most popular and effective forms of chemical control of house flies (Musca domestica). While these baits contain a sucrose phagostimulant, some also contain the bittering agent denatonium benzoate at 20 or 100 ppm, as a feeding deterrent for humans. The response of adult house flies to 10, 100 and, 1000 ppm denatonium benzoate in sucrose solution was compared to response to sucrose only solution using proboscis extension response and no-choice consumption assays. Three house fly strains, DBQB, WD, and UF, each from a different Florida dairy farm, were tested within two generations of collection. Strain DBQB, but not strains WD or UF, had a known history of exposure to toxic baits containing denatonium benzoate, although recent insecticide history was unknown. For males, all strains avoided proboscis extension response and consumption with 1000 ppm, but not with 10 ppm. Males of WD and UF strains, but not DBQB strain showed significantly lower frequency of proboscis extension response at 100 ppm. Males of WD strain, but not DBQB or UF strains, also avoided consuming 100 ppm. For females, the pattern of significance for proboscis extension response was the same for all strains: avoidance for 1000 ppm but not for 10 or 100 ppm. Female consumption was significantly reduced at 1000 ppm for the DBQB and WD strains, but not for the UF strain, but no strain avoided 10 or 100 ppm for consumption. Thus, our results suggest that in some populations of house flies, 100 ppm of denatonium benzoate may reduce consumption by males, although not consumption by females.